Synthesis, Structure and Luminescent Property of Heterometallic Ln(III)–K Complexes with 4,4,4–trifluoro–1–phenyl–1,3–butanedione Ligand - Ha, Phan Thi Thu; Hai, Nguyen Van; Hai, Nguyen Manh; Hien, Dinh Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 2, 2025)
Three heterometallic β–diketonate complexes, [Ln(TFPB) 4 K] (Ln = Eu ( 1 ), Lu ( 2 ), Y ( 3 ); TFPB = 4,4,4–trifluoro–1–phenyl–1,3–butanedione), were synthesized and structurally characterized using ESI–MS, IR and 1 H – NMR spectroscopies. X–ray crystallographic analysis demonstrates that ( 1 ) exists as dimer form in which the Eu 3+ ion was coordinated by four TFPB ligands. The alkali metal K in the complex is stabilized  by electrostatic interactions with O and F atoms of TFPB ligands. The luminescence properties of ( 1 ) were determined using UV–Vis and photoluminescence methods. The results indicate that under 360 nm excitation, the Eu(III) complex emits strong red fluorescence at 616 nm, corresponding to the transition 5 D 0 ® 7 F 2 .